2016
DOI: 10.1136/ejhpharm-2015-000864
|View full text |Cite
|
Sign up to set email alerts
|

Review of structured guides for deprescribing

Abstract: Avoiding inappropriate polypharmacy has become increasingly recognised as a safety imperative for older patient care. Deprescribing is an active process of reviewing all medications being used by individual patients that prompts clinicians to consider which medications have unfavourable risk–benefit trade-offs in the context of illness severity, advanced age, multi-morbidity, physical and emotional capacity, life expectancy, care goals and personal preferences. Structured guides to deprescribing include algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 49 publications
(55 reference statements)
1
53
0
1
Order By: Relevance
“…Many generic (non‐drug specific) deprescribing frameworks have been published . These often provide a stepped approach to deprescribing, highlighting that it is a process (rather than a simple one‐off interaction).…”
Section: Tools To Aid the Overall Process Of Deprescribingmentioning
confidence: 99%
“…Many generic (non‐drug specific) deprescribing frameworks have been published . These often provide a stepped approach to deprescribing, highlighting that it is a process (rather than a simple one‐off interaction).…”
Section: Tools To Aid the Overall Process Of Deprescribingmentioning
confidence: 99%
“…Therefore, it is unclear whether using these tools is likely to result in a meaningful reduction in inappropriate medication use and improve outcomes, or even cause harm . A previous review also noted this limitation . Lack of clinical outcome data and inconsistency in outcome measurement have also been highlighted as limitations in deprescribing studies .…”
Section: Discussionmentioning
confidence: 99%
“…A 2018 systematic review evaluating deprescribing interventions in older persons found that few studies measured clinical outcomes and that none were adequately powered to detect differences in clinical outcomes between intervention and control groups . A number of deprescribing tools have been developed in recent years, but they remain largely untested . Researchers and clinicians should focus on developing quality tools using systematic and explicit methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations